The Importance of Social Networks in the Process of Supporting Sustainable Development - MIHAELA IOANA GURĂU (Global Economic Observer, 2021)
The problems and ideas we classify today under the concept of sustainability have their origins thousands of years ago. The search for a balance between the demand for raw materials for food, clothing, shelter, energy and other goods, as well as awareness of the environmental limits of ecosystems have been a constant concern throughout human history. The emergence of social networks has created huge opportunities for communication and direct interaction with the public, which has proven to be a great advantage in spreading sustainability as a lifestyle among some of the social media users.. Resilience as the ability of a system to annihilate disturbances and to reorganize itself in an attempt to preserve its functions and structure represents, when we talk about sustainability, the relationship between different types of urban hazards, implicitly ecological resilience, resilience of urban and regional economies or of institutions. But people are obliged to help nature in its efforts to reorganize in the face of environmental, social or economic problems. In this sense, in this paper we analyze the role of social networks in the process of supporting sustainable development by presenting a case study for which we used the qualitative research method, and as a technique we used the semi-directional interview.